Nucleotide Sugars in Chemistry and Biology - Satu Mikkola (MDPI, 2022)
Nucleotide sugars have essential roles in every living creature. They are the building blocks of the biosynthesis of carbohydrates and their conjugates. They are involved in processes that are targets for drug development, and their analogs are potential inhibitors of these processes. Drug development requires efficient methods for the synthesis of oligosaccharides and nucleotide sugar building blocks as well as of modified structures as potential inhibitors. It requires also understanding the details of biological and chemical processes as well as the reactivity and reactions under different conditions. This article addresses all these issues by giving a broad overview on nucleotide sugars in biological and chemical reactions. As the background for the topic, glycosylation reactions in mammalian and bacterial cells are briefly discussed. In the following sections, structures and biosynthetic routes for nucleotide sugars, as well as the mechanisms of action of nucleotide sugar-utilizing enzymes, are discussed. Chemical topics include the reactivity and chemical synthesis methods. Finally, the enzymatic in vitro synthesis of nucleotide sugras and utilization of enzyme cascades in the synthesis of nucleotide sugars and oligosaccharides are briefly discussed.